Career plan and related attributes of nurses (Asian Journal of Medical and Biological Research, 2021)
A career is defined as advancing in a chosen job and as a result of that earning more money, taking on more responsibility, gaining more status, power, and respect A descriptive type of cross sectional study was conducted in two tertiary level Government hospitals namely Rajshahi Medical College Hospital (RMCH), Rajshahi and Shaheed Suhrawardy Medical College Hospital (ShSMCH), Sher-E-Bangla Nagar, Dhaka, Bangladesh from 1st January to 31st December, 2019 with the aimed to determine the career plan and related attributes of nurses in a selected tertiary hospital. Study Population was the nurses working in those two hospitals and convenience sampling technique was done, Sample size was 302. After taking written consent from the respondents, data collection was done by face to face interview using a semi-structured questionnaire. The study findings revealed that 94.0% of the respondents have career plan and only 89 respondents were received degree after employment, 43.8% nurses worked in RMCH and 56.2% nurses worked in ShSMCH. From the total respondents, 58.6% respondents expect after completion higher education they will get better job opportunity. Here, 50.0% of the respondent’s reason for no career plan had family problem, 33.3% respondents’ opinion was time consuming and only 16.7% respondents’ opinion was expensive and 56.3% had job satisfaction. Length of service significantly (p